Planowanie przestrzenne jako instrument wdrażania zrównoważonego rozwoju w Polsce - próba oceny - Drzazga, Dominik (Evaluation of the Polish spatial planning system as an instrument for sustainable development, 2007)
The aim of this paper is to answer the ąuestion whether the Polish spatial planning system is a useful tool for sustainable land use and built environment processes, or not? The author presents the thesis that physical, regional and national planning in Poland have plenty of institutional failures. The drawbacks of procedures of planning are intensified by failures of land market. Both are the reasons that in practice spatial planning is unable to create sustainable development and spatial order. In the context of new theories of spatial planning, the author proves the most important conclusions conceming reconstruction of the Polish planning system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 248-257